2016
DOI: 10.1159/000449238
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of an Osmosensitive Cation Channel, Transient Receptor Potential Vanilloid 4, in Rat Vestibular Ganglia

Abstract: Transient receptor potential vanilloid (TRPV) 4 is a nonselective cation channel expressed in sensory neurons such as those in the dorsal root and trigeminal ganglia, kidney, and inner ear. TRPV4 is activated by mechanical stress, heat, low osmotic pressure, low pH, and phorbol derivatives such as 4α-phorbol 12,13-didecanoate (4α-PDD). We investigated the expression of TRPV4 in rat vestibular ganglion (VG) neurons. The TRPV4 gene was successfully amplified from VG neuron mRNA using reverse-transcription polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…arachidonic acid derivatives, changes in osmolarity, endocannabinoids, α-phorbols, proteases and mechanical stimuli) [74][75][76]. TRPV4 mRNA expression has been demonstrated in rodent sensory, trigeminal, dorsal root, vestibular, nodose and jugular ganglia [8,9,[77][78][79][80][81]. However, expression studies were performed on whole ganglia rather than single-cell expression studies on isolated neurons, so expression on non-neuronal cells cannot be ruled out.…”
Section: Trpv4mentioning
confidence: 99%
“…arachidonic acid derivatives, changes in osmolarity, endocannabinoids, α-phorbols, proteases and mechanical stimuli) [74][75][76]. TRPV4 mRNA expression has been demonstrated in rodent sensory, trigeminal, dorsal root, vestibular, nodose and jugular ganglia [8,9,[77][78][79][80][81]. However, expression studies were performed on whole ganglia rather than single-cell expression studies on isolated neurons, so expression on non-neuronal cells cannot be ruled out.…”
Section: Trpv4mentioning
confidence: 99%
“…Previous studies have reported that intraduodenal infusion of glucose in healthy subjects could significantly increase superior mesenteric artery blood flow, and it had been assumed that acute application of glucose and sodium could induce vasorelaxation of mesenteric artery, most likely through NO production (Matheson et al, 1997;Qu et al, 2014;Zani & Bohlen, 2005). However, it is currently accepted that NO mainly regulates the tone of large conduit vessels, whereas EDH plays a dominant role in small resistance vessels such as mesenteric and cardiac arterioles (Crane, Gallagher, Dora, & Garland, 2003;Garland et al, 1995;Godo et al, 2016 (Ma et al, 2013;Seki et al, 2017), and they are osmosensitive or mechanosensitive (Adapala et al, 2016;Kamakura et al, 2016). We initially tested if endothelial TRPV4/Ca 2+ signalling is involved in hyperosmosis-induced EDH signals.…”
Section: Discussionmentioning
confidence: 99%
“…Since the EDH‐associated SK Ca and IK Ca channels in vascular endothelial cells are sensitive to [Ca 2+ ] i , we examined their mechanism of activation. It is well known that the Ca 2+ ‐permeable TRPV1 and TRPV4 channels are functionally expressed in HUVECs (Ma et al, 2013; Seki et al, 2017), and they are osmosensitive or mechanosensitive (Adapala et al, 2016; Kamakura et al, 2016). We initially tested if endothelial TRPV4/Ca 2+ signalling is involved in hyperosmosis‐induced EDH signals.…”
Section: Discussionmentioning
confidence: 99%